Implementasi Teknologi Tepat Guna dalam Mitigasi Banjir Sungai Gambir Tembalang Semarang - Churun Ain; Siti Rudiyanti; Dina Rahayuning Pangestuti; Bragy Nizar Adi Brata (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Flooding in the Tembalang area, particularly around the Gambir River, is a recurring problem every year. This problem is primarily caused by an increase in water discharge that is not balanced with the physical condition of the river, which is experiencing narrowing and silting. Furthermore, the presence of a bridge on Jalan Bulusari also exacerbates the situation because its construction impedes the smooth flow of water. This obstacle is further exacerbated when garbage accumulates and becomes stuck under the bridge, resulting in overflows that inundate the surrounding area. Various self-help efforts have been undertaken by the community, including submitting proposals for bridge reconstruction to relevant agencies, but have not yet produced a tangible impact. This community service activity adopted a Participatory Action Research (PAR) approach, involving the community directly in the planning, decision-making, and implementation of flood mitigation solutions. The main proposed solution is bridge reconstruction to increase river flow capacity and minimize water flow obstructions. As a supporting measure, a sensor-based water level monitoring system has been installed to serve as an early warning for local residents. Furthermore, a waste sorting program has been implemented, providing separate bins for plastic bottles and paper to reduce the potential for river blockages. This participatory approach is expected to not only increase the effectiveness of flood mitigation, but also strengthen community preparedness and resilience to disasters, while providing examples of model solutions that can be replicated in other areas with similar conditions.